Mendorong Prestasi Komunitas Kreatif Dan Kualitas Kemasan Produk UMKM Desa Bojong Kabupaten Kuningan - Haniek Listyorini; Nurdina Prasetyo (BADAN PENERBIT STIEPARI PRESS, 2023)
The Ministry of Tourism and Creative Economy encourages the growth of economic communities in tourism villages based on the creative economy. Since being declared as a creative village in 2022, Bojong village, Kuningan Regency has been encouraged to develop. The problem faced by the creative economy community is that it is not yet popular, product packaging has not met the criteria of the creative economy. This community service activity aims to help increase the popularity of Bojong creative village and standardize MSME products towards creative economy products. The service method is carried out through socialization, FGD, and training. This activity has succeeded in increasing the understanding of the economy community from 50% to 80%, increasing popularity through TV and online media coverage, improving the quality of packaging, export packages and promotional fliers, and obtaining two achievements, namely the district level and provincial level in the culinary field.